Perception of professional Portuguese soccer players about the replacement of leadership with the season underway - a qualitative study - Sousa, H.; Sarmento, H.; Gouveia, É. R.; Clemente, F. M. (International Journal of Performance Analysis in Sport, 2025)
Head Coaches (HCs) and players are the primary agents with the greatest influence on performance in professional soccer. With failure, the common approach is to replace the HC. Little is known about the players` awareness in these situations. This study explored players` understanding of leadership changes. Semi-structured interviews were conducted with 9 Portuguese professional players from five different clubs in the Portuguese top 2 soccer leagues (33.44 ± 1.66 years; 13.33 ± 2.23 professional seasons; 7.33 ± 3.96 career clubs). Interview questions focused on priorities in training sessions, methods and exercises and on concerns, motivations, communication, and leadership style. Interviews were audio-recorded, transcribed and analysed through a content analysis approach. Results were processed through context analysis and a deductive-inductive approach to encode information. Recovering the players` confidence/motivation and assessing the squad capability were the top priorities reported. Players reported increased motivation to train and compete, preferring competitive and less complex exercises. Key concerns included logistical changes and the game model not fitting the players` profile. A more flexible HC, communicative and participative in training, were recommended traits. These insights can provide scientific guidance for inexperienced HCs lacking expertise. Future research should examine the perspectives of HCs, comparing their approaches and methods.